2003
DOI: 10.1061/(asce)0887-3828(2003)17:3(144)
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Recent Bridge Failures in the United States

Abstract: When discussing the infrastructure in America, and more specifically, the problems facing America's infrastructure, bridge failures have been one of the leading problems facing America's infrastructure. Bridge failures often are costly in the commerce foregone, lives lost, and replacement funds required to rebuild the failed vii 2012  Entered the Graduate School at Ohio State University as a Master's candidate for Civil Engineering, Construction Engineering and Management focus  Began work as a transportatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
257
0
19

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 774 publications
(312 citation statements)
references
References 4 publications
1
257
0
19
Order By: Relevance
“…Adverse hydraulic action, including scour, is deemed to have accounted for over 53% of a total of 500 documented bridge failures in the United States between 1989 and 2000 [3]. Larger and more frequent flood flows coupled with aging infrastructure signify that scour analysis and monitoring is becoming increasingly important in modern times [4].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse hydraulic action, including scour, is deemed to have accounted for over 53% of a total of 500 documented bridge failures in the United States between 1989 and 2000 [3]. Larger and more frequent flood flows coupled with aging infrastructure signify that scour analysis and monitoring is becoming increasingly important in modern times [4].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that 53% of 500 bridge failures occurring between 1989 and 2000 in the United States occurred as a result of flooding and/or scour problems [4]. This issue presents a significant cost burden on bridge owners/managers worldwide between inspections, scour protection installation and repairing damage caused by scour [5].…”
Section: Bridge Scourmentioning
confidence: 99%
“…Between 1989 and 2000 there were over 500 bridge collapses in the United States alone (Wardhana & Hadipriono, 2003). River bed scour was responsible for 165 of the failures and ice was the cause of 10 of the collapses (Wardhana & Hadipriono, 2003). In April of 1987, the Schoharie Creek Bridge in New York collapsed due to sediment scour around the bridge pier (Hains & Zabilansky, 2007).…”
Section: Historical Ice Related Disastersmentioning
confidence: 99%
“…Since man has been constructing bridges and crossing structures over river channels, there have been a number of accidents involving ice build up, ice jams and sediment scour. Between 1989 and 2000 there were over 500 bridge collapses in the United States alone (Wardhana & Hadipriono, 2003). River bed scour was responsible for 165 of the failures and ice was the cause of 10 of the collapses (Wardhana & Hadipriono, 2003).…”
Section: Historical Ice Related Disastersmentioning
confidence: 99%